The weeding of Library Materials in University Libraries - Rodríguez Castro, Hernán (1993)
University Libraries, purchased large quantities of information in books, monographs, magazines, videos, etc.., So accumulate a considerable body of library materials, audiovisual and special great value and wealth, however, it is necessary to purge their collections bibliographic to have a refined collection, balanced and consistent with the needs of users express their information.